Workflow, Time Requirement, and Quality of Medication Documentation with or without a Computerized Physician Order Entry System—A Simulation-Based Lab Study - Jungreithmayr, Viktoria; Haefeli, Walter E.; Seidling, Hanna M.; and Implementation Team (Methods of Information in Medicine, 2023)
Background The introduction of a computerized physician order entry (CPOE) system is changing workflows and redistributing tasks among health care professionals.Objectives The aim of this study is to describe exemplary changes in workflow, to objectify the time required for medication documentation, and to evaluate documentation quality with and without a CPOE system (Cerner® i.s.h.med).Methods Workflows were assessed either through direct observation and in-person interviews or through semistructured online interviews with clinical staff involved in medication documentation. Two case scenarios were developed consisting of exemplary medications (case 1 = 6 drugs and case 2 = 11 drugs). Physicians and nurses/documentation assistants were observed documenting the case scenarios according to workflows established prior to CPOE implementation and those newly established with CPOE implementation, measuring the time spent on each step in the documentation process. Subsequently, the documentation quality of the documented medication was assessed according to a previously established and published methodology.Results CPOE implementation simplified medication documentation. The overall time needed for medication documentation increased from a median of 12:12 min (range: 07:29–21:10 min) without to 14:40 min (09:18–25:18) with the CPOE system (p = 0.002). With CPOE, less time was spent documenting peroral prescriptions and more time documenting intravenous/subcutaneous prescriptions. For physicians, documentation time approximately doubled, while nurses achieved time savings. Overall, the documentation quality increased from a median fulfillment score of 66.7% without to 100.0% with the CPOE system (p < 0.001).Conclusion This study revealed that CPOE implementation simplified the medication documentation process but increased the time spent on medication documentation by 20% in two fictitious cases. This increased time resulted in higher documentation quality, occurred at the expense of physicians, and was primarily due to intravenous/subcutaneous prescriptions. Therefore, measures to support physicians with complex prescriptions in the CPOE system should be established.
Keywords: Computerized physician order entry; lab study; medication documentation process; documentation quality; tertiary care